Handbook of research on emerging trends and technologies in library and information science - Kaushik, Anna; Kumar, Ashok, 1973-; Biswas, Payel, 1983- (IGI Global, 2020)
"This book examines the role library and information science professionals play in assessing, understanding, exploring, implementing, and using innovations, trends, and new technologies in the library and information science sector"--